Pengaruh Reinforcement terhadap Peningkatan Disiplin Belajar Siswa Sekolah Menengah Pertama - Riffa Dhil Jannah; Endang Setyaningsih (Indo Publishing, 2026)
Learning discipline is one of the determining factors for students' academic success, but various reports in the field indicate that the level of learning discipline among Junior High School (SMP) students is still relatively low, characterized by late submission of assignments, lack of compliance with class rules, and low consistency in independent learning. One strategy that is theoretically believed to be able to shape and maintain disciplined behavior is the provision of reinforcement by teachers. This study aims to determine whether there is an effect of reinforcement on improving learning discipline in junior high school students. The study used a quantitative approach with a correlational-predictive design. Data were collected through a Likert-scale questionnaire measuring the variables reinforcement (X) and learning discipline (Y), then analyzed using a simple linear regression technique with the help of SPSS. The results of the analysis that reinforcement has a positive and significant influence on student learning discipline, with a coefficient of determination indicating that reinforcement contributes a significant proportion of variance to learning discipline, while the remainder is explained by other factors outside the model. This finding strengthens the assumption of operant conditioning theory that consistent and timely reinforcement can form a more stable pattern of disciplined behavior in students. This study contributes to the literature by presenting quantitative evidence at the junior high school level, which has so far been minimal compared to studies at the elementary school level or descriptive qualitative studies